The Relationship of Core Value and Human Capital Drivers to Improve Organization Results (Case Study at PT Shafira Laras Persada) - Nirmalasari, Healthy; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2014)
SHAF.Corp wants to evaluate and had deeper understanding about core values and human capital drivers’ relationship with results on engagement and  innovation based on employees’ perspectives. The purpose of this research is to identify relationship between Core Values (CV) and Human Capital Drivers (HCD) to Organization Results on engagement and innovation based on employees’ perspectives, identify the most predictor element through indicators of variables and the last is initiate improvement initiatives for managerial implication. 127 employees had been chosen as respondent through cluster random sampling and were asked via questionnaire through 85 questions with Likert scale of 6 to get employees’ perspectives. Questionnaire data processed with path analysis using smartPLS software. Data gathered also through deep interview with related department and literature research to get past and current activities. Based on path analysis revealed positive correlation between CV to HCD (82.5%) and HCD to Results (84.3%). Assertive-AST (62.0%)is the the most predictor that contribute highest coefficient to CV and Knowledge Accessibility (KAC) - 65.0% predict highest coefficient to HCD followed by Leadership Managerial Practices (LMP) - 60.8%. Improvement initiatives to improve Organization Results on Engagement and Innovarion through CV and HCD proposed more focus on CV, KAC, and LMP. Keywords: Islamic Fashion, Core Values, Human Capital Drivers, Engagement, Innovation.